(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Red Gedi Leaves Extract (RGLE) have phytochemicals such as alkaloids, flavonoids, polyphenols, saponins and tannins which known as antidiabetic agents. Study had been done about RGLE (Abelmoschus manihot (L.) Medic) on blood glucose level, 8-hydroxy-deoksiguanosin, malondialdehyde and insulin in diabetic rats (Rattus norvegicus). This study aims to prove the effects of RGLE in blood glucose levels, 8-hydroxy-deoksiguanosin, and malondialdehyde and insulin levels in rats with diabetes induced by streptozotocin and which is the most effective dosage of RGLE. Study used pre and post test design. RGLE obtained by maceration method using by ethanol 96%. There were 120 white male rats which were divided into six treatment groups, each group consisting of 20 individuals. Group I (healthy control), II (negative control) were given by Na-CMC 0.5%. Group III as the positive control were given by glibenclamide, group IV, V, and VI given by RGLE with different doses (150, 300 and 450)mg/kg BW. Animal test were diabetic induced by Streptozotocin with 40 mg/kg BW dosage i.p. Data were analyzed by One Way (ANOVA). The result showed that RGLE can reduced blood glucose levels, 8-hydroxy-deoksiguanosin, and malondialdehyde and increased insulin levels in diabetic rats. The Effective Dosage of RGLE is 150 mg/kg BW.